Temperature controls LasR regulation of piv expression in Pseudomonas aeruginosa - Rachel E. Robinson; Joshua K. Robertson; Samantha M. Prezioso; Joanna B. Goldberg (mBio)
ABSTRACT The opportunistic pathogen Pseudomonas aeruginosa causes debilitating lung infections in people with cystic fibrosis, as well as eye, burn, and wound infections in otherwise immunocompetent individuals. Many of P. aeruginosa’s virulence factors are regulated by environmental cues, such as temperature and cell density. One such virulence factor is protease IV. Prior studies have shown that piv expression is higher at ambient temperatures (22°C–28°C) compared to human body temperature (37°C) and also upregulated by the LasRI quorum sensing system, although it is unclear how. We found that piv expression was thermoregulated at stationary phase, but not exponential phase, and that piv is thermoregulated at the level of transcription. Using a transcriptional reporter for piv, we show that LasR activates piv expression more at 25°C at stationary phase than at 37°C. We show that key components of the LasRI quorum sensing system are not upregulated at 25°C, suggesting that LasR regulatory activity is not higher intrinsically at this temperature. We also identified sequences within the piv promoter that are important for its thermoregulation. We propose that LasR upregulates piv more at 25°C than at 37°C. The finding that temperature controls LasR regulation of piv highlights the complex nature of gene regulatory systems in P. aeruginosa.IMPORTANCEPseudomonas aeruginosa is a versatile opportunistic pathogen capable of causing many different types of infections that are often difficult to treat, such as lung infections in people with cystic fibrosis. Temperature regulates the expression of many virulence factors that contribute to P. aeruginosa’s ability to cause infection, yet our mechanistic understanding of virulence factor thermoregulation is poor. In this study, we show that the virulence factor protease IV is thermoregulated at the level of transcription through the quorum sensing regulator, LasR. Mechanistic studies of virulence factor thermoregulation will expand our understanding of how P. aeruginosa experiences different environments, including the mammalian host. Our work also highlights the importance of growth conditions in studying gene regulation, as it better elucidates the regulation of protease IV by LasR, which was previously not well understood.